2017
DOI: 10.1016/j.dyepig.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photostability of 1,4-bis(5-phenyloxazol-2-yl)benzene (POPOP) structural isomers and their trimethylsilyl derivatives

Abstract: In this work, a versatile synthetic method for preparation of linear phenyloxazoles and their organosilicon derivatives under mild conditions via a combination of van Leusen and direct C-H arylation reactions is reported. It was used for the synthesis of a novel trimethylsilyl (TMS) derivative of blue laser dye 1,4-bis(5-phenyloxazol-2-yl)benzene (POPOP) and its structural isomer 1,4-bis(2-phenyloxazol-5-yl)benzene (isoPOPOP) with and without TMS substituents. All of the compounds demonstrated high photolumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Most probably, the decrease in the luminescence intensity is associated with a destruction of the system of conjugated bonds of the benzothiadiazole fragment during the photo-oxidation. Similar processes of photo-oxidative degradation were observed for compounds containing oxazole fragments (Skorotetcky et al, 2017).…”
Section: Optical Absorption and Luminescencesupporting
confidence: 73%
“…Most probably, the decrease in the luminescence intensity is associated with a destruction of the system of conjugated bonds of the benzothiadiazole fragment during the photo-oxidation. Similar processes of photo-oxidative degradation were observed for compounds containing oxazole fragments (Skorotetcky et al, 2017).…”
Section: Optical Absorption and Luminescencesupporting
confidence: 73%
“…The synthetic scheme of the two kinds of linear phenyloxazoles was exhibited, in which method A (Scheme 18) comprises fewer reaction stages compared with the preparation of the exact 1,4-bis(5phenyloxazol-2-yl)benzene (POPOP) structure (Scheme 18, method B). Due to the concise and efficient synthesis and excellent optical properties as well as high photo-and thermo-stability, the novel luminescent dyes might find broad application in organic photonics [58]. In 2016, Vinary Kumar and co-workers described a novel modified van Leusen protocol for the preparation of 5-(het)aryl oxazoles 73.…”
Section: Developments Of the Van Leusen Oxazole Synthesismentioning
confidence: 99%
“…The synthetic scheme of the two kinds of linear phenyloxazoles was exhibited, in which method A (Scheme 18) comprises fewer reaction stages compared with the preparation of the exact 1,4-bis(5phenyloxazol-2-yl)benzene (POPOP) structure (Scheme 18, method B). Due to the concise and efficient synthesis and excellent optical properties as well as high photo-and thermo-stability, the novel luminescent dyes might find broad application in organic photonics [58]. In the following year, the Ponomarenko group invented various synthetic routes for the preparation of linear phenyloxazoles and their trimethylsilane (TMS) group substituted derivatives, which could serve as the novel luminescent dye under a mild condition, by a combination of the van Leusen process and direct C-H arylation reaction.…”
Section: Developments Of the Van Leusen Oxazole Synthesismentioning
confidence: 99%
“…Recently, linear conjugated oligomers consisting of a combination of various heterocyclic groups, for example, thiophene-phenylenes (Hotta et al, 2004;Sung et al, 2007;Yamao et al, 2007;Postnikov et al, 2014;Kudryashova et al, 2016;Kazantsev et al, 2017b;Parashchuk et al, 2018), furan-phenylenes (Koskin et al, 2017;Kazantsev et al, 2017a;Sonina et al, 2018), oxazole-phenylenes (Yan et al, 2013;Skorotetcky et al, 2017;Sverbil et al, 2020 etc. ) have attracted great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies have shown that an oligomer containing a central BTD fragment, six conjugated thiophene and phenylene groups, and terminal trimethylsilyl substituents crystallizes well from solutions in the form of needle crystals of centimetre scale and is characterized by a high quantum yield of fluorescence in solutions and in the crystalline state (Postnikov et al, 2019b). In terms of optical properties, oligomers consisting of phenylene and oxazole groups are among the most efficient luminophores (Yan et al, 2013;Skorotetcky et al, 2017). In this regard, it is very interesting to develop new molecules based on BTD, oxazole and phenylene groups.…”
Section: Introductionmentioning
confidence: 99%